(untitled) (Journal of actual problems of jurisprudence, 2018)
The article is devoted to one of the most important and fundamental issue of human rights law, namely, the problems of the most vulnerable people to protect the rights – refugees. This article examines the international legal citizenship, ways of acquiring citizenship, as well as the regulation of the legal status of refugees. Historical aspects of occurrence of citizenship, which originate from the time of the French Revolution. We consider the law «On citizenship» in the Republic of Kazakhstan, there are differences related to the scope of rights and duties, determined the nature of relations with the state. The circle of the relationship between state and citizen, studied the constitutional rights and duties of the person. Authors affect the acquisition, change and loss of nationality, legal capacity and capacity to act. The paper presents a comparative legal analysis of the legislation of foreign countries on citizenship issues. The authors identify citizenship as a «special status», purchased by individuals. Key words: citizenship, refugees, human rights and citizens’ legal status.